Strategi BUMDes untuk Meningkatkan Kolaborasi Lintas Agama: Studi Kasus di Desa Kulu, Pekalongan - Hasanah, Hilmatul; Jupriyanti, Soffiyana Dwi (Indonesian Journal Publisher, 2023)
The purpose of this study is to examine how the cooperation between Village Owned Enterprises (BUMDes) of Kulu and local entrepreneur, Mr. Joko, in managing the Ratu Bali Coffee (RBC) cafe in Kulu Village. The research methods used are case studies through interviews, observations, and documentation. The results of the study showed that this cooperation resulted in benefits for various parties, namely BumDes Kulu and Pak Joko, as well as the surrounding communities. Where they get the opportunity to grow their business, and the surrounding community gets the opportunity to engage in its economic and social activities. In addition, this cooperation also demonstrates religious tolerance, where RBC cafes are able to create a comfortable environment for everyone regardless of religious and cultural background. So that this cooperation can be maintained and improved by improving the quality of products, services, expanding social networks, and developing more innovative and creative cafes.